International Accounting Harmonization of Cash Flow Reporting Practices: Evidence From the Largest Italian and Spanish Companies - Paolone, Francesco; Becerra, Jaime Gregorio Cabanellas (International Journal of Accounting and Financial Reporting, 2022)
This paper investigates the phenomenon of accounting harmonization among Italian and Spanish entities that adopt IAS/IFRS, focusing on the cash flow reporting practices (IAS 7). We provide empirical evidence at the European level by analysing the accounting harmonization of IAS 7 adoption. Specifically, by using the C index of Van der Tas, we analyse the Cash Flow Statements (CFSs) published in 2020 of the largest companies that operate in Italy and Spain, respectively listed in FTSE MIB40 and IBEX35. Overall, the empirical findings indicate great levels of harmonization in applying IAS 7 emerged by the analysis of CFSs in the annual reports of 2020. Italian and Spanish companies show similar results on IAS 7 harmonization. The level of harmonization could be improved in the future across different companies of various EU countries, necessitating further work by the IASB to reduce alternative methods allowed in IAS/IFRS standards. The aim of this work is to investigate how IAS 7 allows different options for reporting entities’ cash flows as well as to verify the level of harmonization of the largest Italian and Spanish groups. Finally, we address solutions to make CFSs more comparable among entities that belong in different EU countries.